Structural and functional features of Fronting in English versus Vietnamese equivalents. M.A. Thesis Linguistics: 60 22 02 01 - Nguyễn, Thị Ái Anh (ĐHNN, 2017)
Fronting seems to be a new concept for English learners and teachers although it can be used unconsciously in daily life. Research into fronting in English and “khởi ngữ” in Vietnamese are numerous; however, no research has been done into the similarities and differences in this linguistic phenomenon in the two languages. This research is carried out to provide a more comprehensive understanding of “fronting” in English and “khởi ngữ” in Vietnamese.